Polymer decoration on carbon nanotubes via physical vapor deposition - Li, Lingyu (Langmuir : the ACS journal of surfaces and colloids, 2007)
The polymer decoration technique has been widely used to study the chain folding behavior of polymer single crystals. In this article, we demonstrate that this method can be successfully adopted to pattern a variety of polymers on carbon nanotubes (CNTs). The resulting structure is a two-dimensional nanohybrid shish kebab (2D NHSK), wherein the CNT forms the shish and the polymer crystals form the kebabs. 2D NHSKs consisting of CNTs and polymers such as polyethylene, nylon 66, polyvinylidene fluoride and poly(L-lysine) have been achieved. Transmission electron microscopy and atomic force microscopy were used to study the nanoscale morphology of these hybrid materials. Relatively periodic decoration of polymers on both single-walled and multi-walled CNTs was observed. It is envisaged that this unique method offers a facile means to achieve patterned CNTs for nanodevice applications